Characheristics of intimate partner femicide in Slovenia - Podreka, Jasna (Annales. Series historia et sociologia, 2019)
Based on the analyzed cases in the research sample the author demonstrates that intimate partner homicides of women in Slovenia are distinctly gendered criminal offences and that Slovenia does not differ significantly in this respect from other countries. In Slovenia as well as in the majority of other countries almost half of homicides of women are committed by a former or current spouse or intimate partner. The analysis also shows that the basis of these acts are strong traditional or patriarchal attitudes of perpetrators on partner relationships and gender roles and especially male feelings of the ownership of their female partners.
Keywords: femicid; intimnopartnerski odnosi; intimnopartnersko nasilje; Moški; Nasilje; partnerske zveze; spolna neenakost; Umori; Ženske